Semantics of the Spring Rites Related to Marzanna and Jarilo (about the Reconstruction of the "Proto-Slavic Text") - Łuczyński, Michał (Respectus Philologicus, 2006)
The article is an attempt to summarize and specify the former proto-Slavic mythology surveys on the divine siblings and the death of God of Harvest myths. The sources used in the study include historical and ethnographical sources, folk songs lyrics, and archeological findings. The study makes it possible to establish the attributes and functions of pagan gods and to find plots and individual myth sequences. This results in the mythical plot reconstruction. There are three stages of proceedings: the presentation of the sources, the semantics of the image establishment, and the reconstruction of the proto-Slavic myth of the dying god.